William Thomas Sampson correspondence - Sampson, William Thomas, 1840-1902.
Letter written by Sampson to John Davis Long, secretary of the navy, describing the defeat of the Spanish fleet at the battle of Santiago de Cuba during the Spanish-American War.
Typewritten transcript.
Naval officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Long, John Davis, -- 1838-1915 -- Correspondence; United States. -- Navy -- History -- Spanish-American War, 1898.; Spain. -- Armada; Santiago, Battle of, Santiago de Cuba, Cuba, 1898.; Spanish-American War, 1898 -- Naval operations; Naval officers